Teachers' and Students' Perceptions of Health Management Policies in Madrasah Environments: An Educational Ethnography in East Java - Juni Iswanto (JM-NU: Jurnal Studi Manajemen Pendidikan Islam, 2025)
Health management in Indonesian madrasahs faces significant cultural and structural barriers, including fragmented policies, resource constraints, and tensions between religious norms and public health imperatives. This educational ethnography examines how stakeholder perceptions shape the effectiveness of health policies in East Javanese Islamic schools. Over six months, the study employed participant observation, semi-structured interviews (n=32), and focus groups (n=8) across three madrasah levels (MI, MTs, MA) in East Java. Findings reveal a critical disconnect: while national policies like UKS (Usaha Kesehatan Sekolah/School Health Efforts) are implemented top-down, teachers and students perceive them as culturally misaligned and administratively burdensome. Notably, Islamic principles strengthened acceptance of hygiene and nutrition initiatives—e.g., handwashing protocols integrated into thaharah (ritual purity) lessons achieved 89% compliance. However, mental health policies faced persistent stigma, with 74% of teachers avoiding discussions due to perceptions of psychological struggles as spiritual weakness (dha'if al-iman). Students expressed strong preferences for participatory approaches, proposing peer-led "Health Muhadharah" (religious lectures) to replace didactic modules. The study concludes that effective health management requires: (1) cultural alignment of health protocols with Islamic ethics (e.g., framing mental health support as ihsan/excellence in self-care), and (2) co-creation of policies with stakeholders to ensure local relevance. Recommendations include decentralizing policy design to involve madrasah councils (syura) and leveraging Islamic concepts like maslaha (public interest) to overcome resistance. This underscores the necessity of context-responsive strategies in Muslim educational settings globally.